Home ownership. Getting in, getting from, getting out. Part III - Doling, John (IOS Press, 2013)
This book provides an overview of the effects of home ownership, a housing sector that has grown rapidly in recent years in many countries, not least because this is normally encouraged by governments. The first part of the subtitle, ‘Getting in’, refers to processes in the development of the homeownership stock including problems of access, which in turn implies issues of affordability, the viability of financial institutions and subsidies. ‘Getting from’ indicates that this form of housing tenure may provide households with advantages such as wealth accumulation and independence that may not be available to tenants. Finally, the last section ‘getting out’ refers to the risks associated with home ownership such as the fact that their tenure positions may be founded on their ability to meet loan repayments. This publication is a follow-up to Home ownership: Getting in, getting form and getting out, parts I and II, and is a result of the conference ‘Building on home ownership; housing policies and social strategies’ in Delft, organized by the ENHR working group Home ownership & Globalisation and hosted by OTB Research Institute for Housing, Urban and Mobility Studies, Delft University of Technology. Part III provides an overview of the most recent research results in this field.